Impact of Water Column Acidification on Protozoan Bacterivory at the Lake Sediment-Water Interface - Tremaine, Sarah C. (1991)
Although the impact of acidification on planktonic grazer food webs has been extensively studied, little is known about microbial food webs either in the water column or in the sediments. Protozoon-bacterium interactions were investigated in a chronically acidified (acid mine drainage) portion of a lake in Virginia. We determined the distribution, abundance, apparent specific grazing rate, and growth rate of protozoa over a pH range of 3.6 to 6.5. Protozoan abundance was lower at the most acidified site, while abundance, in general, was high compared with other systems. Specific grazing rates were uncorrelated with pH and ranged between 0.02 and 0.23 h(-1), values similar to those in unacidified systems. The protozoan community from an acidified station was not better adapted (P = 0.95) to low-pH conditions than a community from an unacidified site (multivariate analysis of variance on growth rates for each community incubated at pHs 4, 5, and 6). Both communities had significantly lower (P < 0.05) growth rates at pHs 4 and 5 than at pH 6. Reduced protozoan growth rates coupled with high grazing rates and relatively higher bacterial yields (ratio of bacterial-protozoan standing stock) at low pH indicate reduced net protozoan growth efficiency and a metabolic cost of acidification to the protozoan community. However, the presence of an abundant, neutrophilic protozoan community and high bacterial grazing rates indicates that acidification of Lake Anna has not inhibited the bacterium-protozoon link of the sediment microbial food web.